2018
DOI: 10.1101/248112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of sexually-transferred steroids inAnophelesmosquitoes

Abstract: Human malaria, which remains a major public health problem, is transmitted by a subset of Anopheles mosquitoes belonging to only three out of eight subgenera: Anopheles, Cellia and Nyssorhynchus. Unlike almost every other insect species, it was shown that males of some Anopheles species produce and transfer steroid hormones to females during copulation and that this transfer mediates reproductive changes. Steroids are consequently seen as a potential target for malaria vector control. Here, we analysed the evo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Together, these observations trace the emergence along the mosquito phylogeny and coevolutionary dynamics of important reproductive genes and traits that may be linked to differences in disease-vector capacity observed today. However, examining a larger set of mosquito species (three Nyssorhynchus, five Anopheles, and eight Cellia) suggested that sexually transferred steroids and their effects on female behaviour did not correlate with the transmission of malaria parasites [104]. Recent largerscale mozomics functional assays are also starting to exploit the available genomes and their annotations to bring an evolutionary perspective to interpreting transcriptomics results from more than a single species, for example, in the context of sex-and tissue-biased gene expression in anophelines [17,18] and culicines [105].…”
Section: Outstanding Questionsmentioning
confidence: 98%
“…Together, these observations trace the emergence along the mosquito phylogeny and coevolutionary dynamics of important reproductive genes and traits that may be linked to differences in disease-vector capacity observed today. However, examining a larger set of mosquito species (three Nyssorhynchus, five Anopheles, and eight Cellia) suggested that sexually transferred steroids and their effects on female behaviour did not correlate with the transmission of malaria parasites [104]. Recent largerscale mozomics functional assays are also starting to exploit the available genomes and their annotations to bring an evolutionary perspective to interpreting transcriptomics results from more than a single species, for example, in the context of sex-and tissue-biased gene expression in anophelines [17,18] and culicines [105].…”
Section: Outstanding Questionsmentioning
confidence: 98%